The Influence of Organizational Culture and Change Management on Company Performance Through Competitive Advantage at PT. Sarana Abadi Makmur Bersama - Purwanto Aji Kusuma; Bomer Pasaribu; Fajar Cahyo Utomo (Krisnadwipayana International Journal of Management Studies, 2023)
This research aims to determine the influence of organizational culture and change management through competitive advantage on company performance at PT. Sarana Abadi Makmur Bersama. The research was carried out using a quantitative approach. The population is 435 employees with a sample of 87 respondents. The data collection technique uses a questionnaire which will be distributed to respondents by random sampling. Data analysis techniques use descriptive analysis, path analysis, regression analysis, and t he Sobel test. The conclusion of the research is that competitive advantage is able to mediate organizational culture and change management on company performance at PT. Sarana Abadi Makmur Bersama. The main findings based on statistical results show that the greatest influence is from direct influence, namely: the change management variable with a beta value of 0.395 then organizational culture with a beta value of 0.297. The suggestion for companies is to focus more on improving change management and organizational culture which will make a greater contribution to improving company performance and increasing the company's competitive advantage.